Neuropsychological characterization of three adolescent females with anti-NMDA receptor encephalitis in the acute, post-acute, and chronic phases: an inter-institutional case series. Issue 1 (2nd January 2017) - Hinkle, Clayton D.; Porter, James N.; Waldron, Eric J.; Klein, Hannah; Tranel, Daniel; Heffelfinger, Amy
Abstract: Objective : Anti- N -methyl-D-aspartate (anti-NMDA) receptor encephalitis is an acute, immune-mediated paraneoplastic syndrome that often presents with psychobehavioral changes, abnormal movements, autonomic instability, seizures, and cognitive dysfunction. While the disease continues to be more readily identified and appropriately treated, the course of cognitive deficits from the acute to post-acute to chronic phase has not been well described, particularly in the pediatric population. This case series describes the neuropsychological functioning of three adolescent females with anti-NMDA receptor encephalitis from its early presentation to long-term follow-up.Method : All three cases are adolescent females with antibody-confirmed anti-NMDA receptor encephalitis. A review of the literature is provided summarizing the disorder and its known cognitive sequelae, pathophysiology, treatment, and prognostic factors, as well as each patient's relevant history, symptom presentation, and disease course. Neuropsychological functioning of each patient was evaluated from her initial inpatient hospitalization to long-term follow-up (3.5–12 months after acute evaluation).Results : All three patients demonstrated clear improvement in cognitive functioning during the course of their recovery, though selected deficits in executive functioning, fine motor dexterity, language, and memory were observed at long-term follow-up in some of our patients.Conclusions : Findings are consistent with studies in adults that found cognitive deficits following anti-NMDA receptor encephalitis. Though gradual recovery was noted over time, all three patients reported no clinically significant difficulties during their final evaluation, despite showing mild impairment in some areas, emphasizing the importance of ongoing neuropsychological follow-up.